The effect of natural and anthropogenic nutrient and sediment loads on coral oxidative stress on runoff-exposed reefs. (July 2021) - Baird, Mark E.; Mongin, Mathieu; Rizwi, Farhan; Bay, Line K.; Cantin, Neal E.; Morris, Luke A.; Skerratt, Jennifer
Abstract: Recently, corals on the Great Barrier (GBR) have suffered mass bleaching. The link between ocean warming and coral bleaching is understood to be due to temperature-dependence of complex physiological processes in the coral host and algal symbiont. Here we use a coupled catchment-hydrodynamic-biogeochemical model, with detailed zooxanthellae photophysiology including photoadaptation, photoacclimation and reactive oxygen build-up, to investigate whether natural and anthropogenic catchment loads impact on coral bleaching on the GBR. For the wet season of 2017, simulations show the cross-shelf water quality gradient, driven by both natural and anthropogenic loads, generated a contrasting zooxanthellae physiological state on inshore versus mid-shelf reefs. The relatively small catchment flows and loads delivered during 2017, however, generated small river plumes with limited impact on water quality. Simulations show the removal of the anthropogenic fraction of the catchment loads delivered in 2017 would have had a negligible impact on bleaching rates. Highlights: Coral bleaching occurred on the GBR in 2017, a year with small river plumes. Natural and anthropogenic catchment loads are also reduced in low flow years. In 2017, our model predicts coral oxidative stress had a cross-shelf gradient. In 2017 we predict anthropogenic loads had negligible impact on oxidative stress. Further work needed on effects of catchment loads on recovery from coral bleaching.